PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IX SMPN - Aprilia, Vivi (Departemen Matematika, 2023)
Learning outcomes refer to the measurable accomplishments of pupils that serve as indicators of whether or not the educational goals in the field of mathematics have been successfully attained. However, it is evident that the learning results of Class IX SMPN exhibit a significant deficiency in terms of academic achievement. This phenomenon can be attributed to the adoption of a learning approach that lacks student engagement in the learning process. In order to address these challenges, the implementation of the Discovery Learning approach is employed. The present study used a quasi-experimental approach with a randomised control group posttest only. The research findings reveal that the hypothesis test yielded a P-value of 0.001, suggesting that the null hypothesis ( ) should be rejected. Therefore, it can be inferred that the learning outcomes of ninth-grade students at SMPN, while utilising the Discovery Learning instructional approach, exhibit a higher level of proficiency compared to those who follow conventional learning model.Keywords. –Discovery Learning, Mathematics, learning outcomes